2009
DOI: 10.1182/blood-2008-05-154302
|View full text |Cite
|
Sign up to set email alerts
|

Population-specific genetic variants important in susceptibility to cytarabine arabinoside cytotoxicity

Abstract: Cytarabine arabinoside (ara-C) is an antimetabolite used to treat hematologic malignancies. Resistance is a common reason for treatment failure with adverse side effects contributing to morbidity and mortality. Identification of genetic factors important in susceptibility to ara-C cytotoxicity may allow for individualization of treatment. We used an unbiased wholegenome approach using lymphoblastoid cell lines derived from persons of European (CEU) or African (YRI) ancestry to identify these genetic factors. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 49 publications
2
113
1
Order By: Relevance
“…Our laboratory found no relationship between EBV copy number or ATP levels and cellular sensitivity to drugs (A. L. Stark, W. Zhang, S. Mi, S. Duan, P. H. O'Donnell, R. S. Huang, M. E. Dolan, submitted). However, we did observe a significant correlation between cellular growth rate and sensitivity to chemotherapy that is not surprising, because many chemotherapeutic drugs are designed against rapidly growing cells (Huang et al, 2008c;Hartford et al, 2009). Therefore, genetic variants associated with sensitivity to chemotherapeutic agents may act through their association with growth rate.…”
Section: Experimental Artifacts and Confoundersmentioning
confidence: 71%
See 1 more Smart Citation
“…Our laboratory found no relationship between EBV copy number or ATP levels and cellular sensitivity to drugs (A. L. Stark, W. Zhang, S. Mi, S. Duan, P. H. O'Donnell, R. S. Huang, M. E. Dolan, submitted). However, we did observe a significant correlation between cellular growth rate and sensitivity to chemotherapy that is not surprising, because many chemotherapeutic drugs are designed against rapidly growing cells (Huang et al, 2008c;Hartford et al, 2009). Therefore, genetic variants associated with sensitivity to chemotherapeutic agents may act through their association with growth rate.…”
Section: Experimental Artifacts and Confoundersmentioning
confidence: 71%
“…Another phenotype to consider is measurement of conversion of parent drug to active metabolite. This has been effectively analyzed in the case of methotrexate glutamation (Masson et al, 1996) and the chemotherapeutic AraC, in which the amount of active metabolite (AraCTP) was associated with a specific genotype within an important drug-metabolizing gene (Hartford et al, 2009).…”
Section: A Developing a Cell-based Model Systemmentioning
confidence: 99%
“…Our group has previously observed in vitro population differences in cellular sensitivity to carboplatin, 25 daunorubicin 25 and araC 26 between the CEU and YRI samples. In this study, we evaluated whether differentially expressed miRNAs contribute to these observed ethnic differences in drug sensitivity.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…We have reported in vitro population differences in cellular sensitivity to carboplatin, 25 daunorubicin 25 and araC 26 between the CEU and YRI samples. Cellular sensitivity to these chemotherapeutic agents-quantified by IC 50 (the concentration required to inhibit 50% of cell growth) for carboplatin and daunorubicin, along with AUC (area under the drug concentration cellular percent survival curve) for araC-was evaluated.…”
Section: Samplesmentioning
confidence: 99%
“…Recent efforts have been aimed at using genome-wide approaches in pharmacogenomic discovery both in patients (4)(5)(6) and in cell-based models (7)(8)(9)(10)(11). The majority of genome-wide significant markers identified in patients through genome-wide association studies (GWASs) were for those rare but serious adverse events, such as the flucloxacillin-induced liver injury and statin-induced myopathy (5).…”
mentioning
confidence: 99%